Komunitas Goa Batu Kapal dalam Mengembangkan Pariwisata Berkelanjutan di Kecamatan Sangir Balai Janggo Kabupaten Solok Selatan (2017-2023) - Komala Desi, Gita Fitri; Fatimah, Siti (Jurusan Sejarah FIS UNP, 2025)
Local communities have a key role ini developing sustainable tourism. The batu kapal cave destination has great tourism potential, but it needs to be well managed to improve its quality and ettractiveness. This research can help identitify effective development strategies. This study discusses the role of the batu kapal cave destination community in developing sustainable tourism in sangir balai janggo district, south solok regency from 2017 to 2023. This study uses a historical method consisting of four techniques including heuristics, source criticism, interpretation, and historiography. Data were obtained from community documents, community decrees from the village head’s office, community membership structures, and photo documentation. To obtain oral sources, interviews ewre conducted with members of the tour guide community, the village head of sungai kunyit barat and staff. The results of this study are the active role of the tour guide community to provide education to the community to care about the natural potential that exsists in their residential environment, at the beginning of its inauguration in 2017 a tour guide community was formed to be able to maximize management, in the following year there was already an educational curruculum to be distributed to the community and obtained commensurate results as evidenced by the many improvements in facilities and services provided to tourists after the training for guides. It is necessary to immediately form a homestay community in order to maximize the function and batu kapal cave tourist destination. With yhe existence od this homestay community, it is hoped that it can become a new attraction for tourists to visit the batu kapal cave destination